Colombiana [videorecording (DVD)] - Megaton, Olivier, 1965-; Saldana, Zoë, 1978-; Mollà, Jordi; James, Lennie (Sony Pictures Home Entertainment, 2011)
" ... a young woman ... has grown up to be an assassin after witnessing the murder of her parents as a child. Turning herself into a professional killer, she remains focused on her ultimate goal: to hunt down and get revenge on the mobster responsible for her parents' deaths"--Container.